Potensi Waste Organic Product (WOP) FST 1310 terhadap Pertumbuhan Candida albicans Penyebab Kandidiasis: Potential of the Waste Organic Product (WOP) FST 1310 on the Growth of the Fungi Candida albicans Causes Candidiasis - Ramadhan, Firdaus; Ghoza, Muhammad Radian; Haribowo, Dinda Rama; Sholeha, Dania Refia Riska; Kartika; Lestari, Anggita Rana Sasmita; Fikriwansyah, Aswir; Putri, Lily Surayya Eka; Ramadhani, Lidia Anggita; Sugoro, Irawan (Jurnal Sumberdaya Hayati, 2025)
Candida albicans is an agent that causes candidiasis which can cause health problems in human’s organs. This study aims to determine the antifungal activity and inhibition zone diameter of Waste Organic Product (WOP) FST 1310 against Candida albicans. This type of research is experimental, using the Kirby-Bauer agar diffusion method with 6 treatments: P1: 100%, P2: 80%, P3: 60%, and P4: 40%, along with 2 controls, P5: nystatin (positive control) and P6: distilled water (negative control). The results showed that the WOP FST 1310 from orange peel had a larger inhibition zone diameter compared to the vegetable-derived. For the vegetable-derived eco-enzyme, the highest inhibition zone diameter was at a 100% concentration with an average of 3.7 mm. Meanwhile, for the orange peel eco-enzyme, the highest inhibition zone diameter was at a 40% concentration with an average of 5.3 mm.